Quantumscapes : the art of Stephan Martiniere. - Martiniere, Stephan, ....- (Culver City : Designstudio, 2006)
Following his previous book, Quantum Dreams, Quantumscapes is a stunning new visionary collection of sci-fi book cover paintings, commercial and film art, video game designs, and never before-seen artwork from the fantastic imagination of acclaimed artist Stephan Martiniere.